Spatio-temporal data model and query language for biodiversity data - Wahid, Mohd. Taib; Kamruzzaman, A. Z. M.; Mohamed Shariff, Abdul Rashid; Napis, Suhaimi (Penerbit UTM Press, 2005)
A Spatio-temporal data model and query language for biodiversity is growing importance to the biodiversity data management, forest and environment control. Spatio-temporal data model and query language have received much attention in the database research community because of their practical importance and interesting challenges they pose. This paper discusses about spatio-temporal information, query language and problems with existing models. In this paper our main objective to minimile the extension required in SQL language. This paper also focuses on the unified models of space and time using object-relation approach. In particular, we propose a conceptual object- relational spatial temporal data model based on Donna J. Peuquet's pyramid framework. SpatioÂ¬temporal queries are expressed by user defined aggregates, such as duration and during temporal relationships. Therefore, query language (such as SQL") or other relational languages are required to support spatio-temporal queries for the biodiversity data model.